Pharmacological Properties of Geraniol – A Review - Lei, Yu; Fu, Peng; Jun, Xie; Cheng, Peng (Planta Medica, 2019)
Geraniol is an acyclic isoprenoid monoterpene isolated from the essential oils of aromatic plants including Cinnamomum tenuipilum, Valeriana officinalis, and several other plants. The limited source of geraniol from plant isolation cannot fulfill the great demand from the flavor and fragrance industries, which require maximizing geraniol production through biotechnology processes. The diverse activities of geraniol suggested that geraniol could treat various diseases as a promising drug candidate. In order to evaluate the potential of geraniol applied in a clinical trial, this review aims at providing a comprehensive summary of the pharmacological effects of geraniol. The publications retrieved from PubMed, ScienceDirect, Springer, and Wiley databases were collected and summarized for the last 6 years. Then, the potential application of geraniol as a drug is discussed based on its pharmacological properties, including antitumor, anti-inflammatory, antioxidative, and antimicrobial activities, and hepatoprotective, cardioprotective, and neuroprotective effects. Hence, this review aims at providing evidence of the pharmacological activities of geraniol in the context of further development as a drug candidate in clinical application.
Keywords: geraniol; essential oil; pharmacology; monoterpene